Characterization of MSW rejected fractions to fulfill RDF requirements and utilization - Brás, Isabel (2017)
In order to fulfil European and Portuguese legal requirements, adequate alternatives to traditional municipal waste landfilling must be found namely concerning organic wastes and others susceptible of valorisation. According to the Portuguese Standard NP 4486:2008, refuse derived fuels (RDF) classification is based on three main parameters: lower heating value (considered as an economic parameter), chlorine content (considered as a technical parameter) and mercury content (considered as an environmental parameter). The purpose of this study was to characterize the rejected streams resulting from the mechanical treatment of unsorted municipal solid waste, from the plastic municipal selective collection and from the composting process, in order to evaluate their potential as RDF. To accomplish this purpose six sampling campaigns were performed. Chemical characterization comprised the proximate analysis – moisture content, volatile matter, ashes and fixed carbon, as well as trace elements. Physical characterization was also done. To evaluate their potential as RDF, the following parameters established in the Portuguese standard were also evaluated: heating value and chlorine content. As expected, results show that the refused stream from mechanical treatment is rather different from the selective collection rejected stream and from the rejected from the compost screening in terms of moisture, energetic matter and ashes, as well as heating value and chlorine. Preliminary data allows us to conclude that studied materials have a very interesting potential to be used as RDF. In fact, the rejected from selective collection and the one from composting have a heating value not very different from coal. Therefore, an important key factor may be the blending of these materials with others of higher heating values, after pre-processing, in order to get fuel pellets with good consistency, storage and handling characteristics and, therefore, combustion behavior.